Combinatorial Treatment of Human Cardiac Engineered Tissues With Biomimetic Cues Induces Functional Maturation as Revealed by Optical Mapping of Action Potentials and Calcium Transients - Wong, Andy On-Tik; Wong, Nicodemus; Geng, Lin; Chow, Maggie Zi-ying; Lee, Eugene K.; Wu, Hongkai; Khine, Michelle; Kong, Chi-Wing; Costa, Kevin D.; Keung, Wendy; Cheung, Yiu-Fai; Li, Ronald A. (Frontiers in Physiology, 2020)
Although biomimetic stimuli, such as microgroove-induced alignment (μ), triiodothyronine (T3) induction, and electrical conditioning (EC), have been reported to promote maturation of human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs), a systematic examination of their combinatorial effects on engineered cardiac tissue constructs and the underlying molecular pathways has not been reported. Herein, human embryonic stem cell-derived ventricular cardiomyocytes (hESC-VCMs) were used to generate a micro-patterned human ventricular cardiac anisotropic sheets (hvCAS) for studying the physiological effects of combinatorial treatments by a range of functional, calcium (Ca2+)-handling, and molecular analyses. High-resolution optical mapping showed that combined μ-T3-EC treatment of hvCAS increased the conduction velocity, anisotropic ratio, and proportion of mature quiescent-yet-excitable preparations by 2. 3-, 1. 8-, and 5-fold (>70%), respectively. Such electrophysiological changes could be attributed to an increase in inward sodium current density and a decrease in funny current densities, which is consistent with the observed up- and downregulated SCN1B and HCN2/4 transcripts, respectively. Furthermore, Ca2+-handling transcripts encoding for phospholamban (PLN) and sarco/endoplasmic reticulum Ca2+-ATPase (SERCA) were upregulated, and this led to faster upstroke and decay kinetics of Ca2+-transients. RNA-sequencing and pathway mapping of T3-EC-treated hvCAS revealed that the TGF-β signaling was downregulated; the TGF-β receptor agonist and antagonist TGF-β1 and SB431542 partially reversed T3-EC induced quiescence and reduced spontaneous contractions, respectively. Taken together, we concluded that topographical cues alone primed cardiac tissue constructs for augmented electrophysiological and calcium handling by T3-EC. Not only do these studies improve our understanding of hPSC-CM biology, but the orchestration of these pro-maturational factors also improves the use of engineered cardiac tissues for in vitro drug screening and disease modeling.